If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -9 + 3x + -5 + x = 7x + 2 Reorder the terms: -9 + -5 + 4x + 3x + x = 7x + 2 Combine like terms: -9 + -5 = -14 -14 + 4x + 3x + x = 7x + 2 Combine like terms: 4x + 3x = 7x -14 + 7x + x = 7x + 2 Combine like terms: 7x + x = 8x -14 + 8x = 7x + 2 Reorder the terms: -14 + 8x = 2 + 7x Solving -14 + 8x = 2 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -14 + 8x + -7x = 2 + 7x + -7x Combine like terms: 8x + -7x = 1x -14 + 1x = 2 + 7x + -7x Combine like terms: 7x + -7x = 0 -14 + 1x = 2 + 0 -14 + 1x = 2 Add '14' to each side of the equation. -14 + 14 + 1x = 2 + 14 Combine like terms: -14 + 14 = 0 0 + 1x = 2 + 14 1x = 2 + 14 Combine like terms: 2 + 14 = 16 1x = 16 Divide each side by '1'. x = 16 Simplifying x = 16
| 0.6666667x+6=0.5x+0.25x | | g(h)=-x^2+x-6 | | x^2+y^2-4x-6y+8=0 | | a-3b-2a= | | 25x-30=10x | | x^2+y^2-4x+6y+8=0 | | -10-(-2)= | | 143-2x=43x+18 | | 2.3x-5.4=-10 | | 7(x-3)-4x=-16 | | (x+1)=0 | | (2x+9)=x-3 | | 6x+18y=24 | | 18x+6y=24 | | 8(3n-2)= | | 14-10x=48-24x | | 6x+16-x=7x+4 | | 3.2= | | 6(-2x-1)=-11(x+1) | | H+6=-22 | | -96-7x=9x+13 | | 3(y-4)=y-6 | | Ay+6=14 | | 6x+3.50=33.20 | | 9-3r=13 | | 6x+1=-92-7x | | 3(2x+1)-5=4(x-3) | | 2t-2y= | | y=x^3+7x^2-245x+35 | | 18=-1.8 | | -52-3=3x+20 | | 2x+15=63-5x |